Exploring vaccination attitudes in African communities in Canada: A mixed-methods study protocol - Obidimma Ezezika; Zantae Pellitier; Sonia Muhimpundu; Christian Daboud; Meron Mengistu; Omolola Olorunbiyi; Christian Hines; Mekoya Wondrad; Joanne Kearon; Reforce Okwei; Kingsley Anukam; Dominic Alaazi; et al. (PLoS ONE, 2025)
Introduction Vaccine hesitancy is a complex issue influenced by many interacting factors. While literature on its contributing causes continues to expand, there is limited research on the contextual and cultural dynamics that shape vaccine hesitancy among African-born individuals in Canada. Identifying and understanding these factors is critical in developing targeted health interventions that address specific barriers to vaccination within this community. The study aims to explore the unique socio-cultural and context-specific elements of vaccine hesitancy among African community members living in Canada. Methods and analysis The study will use a mixed-methods approach to investigate vaccine hesitancy among African community members living in Southwestern Ontario. In the qualitative study, we will conduct semi-structured interviews and participatory focus groups within each of the selected study areas: London, Windsor and Chatham-Kent. The qualitative data will be collected, transcribed and then analyzed thematically using NVivo 12. For the quantitative study, we will provide participants with surveys to accurately assess the predictors of vaccine hesitancy. The quantitative data will be analyzed using logistic regression to explore how socio-cultural influences, trust, and accessible information impact vaccine hesitancy. Discussion This study addresses a significant gap in existing literature by providing cultural and contextual insights on the drivers of vaccine hesitancy among African-born individuals. Using a mix-method design, the study offers a rich understanding of the influences shaping vaccine decision-making. The findings will support the development of health policies and interventions aimed at improving overall health outcomes for African communities within Canada.